Predation on the lizard Polychrus acutirostris (Squamata, Polychrotidae) by the curl-crested jay Cyanocorax cristatellus (Aves, Corvidae) in the Cerrado of Central Brazil - Frederico Gustavo Rodrigues França; Vívian da Silva Braz (Biotemas)
http://dx.doi.org/10.5007/2175-7925.2009v22n3p243